Metode Ceramah Plus Diskusi dan Tugas Untuk Meningkatkan Aktivitas Belajar Siswa - Hana Maurin; Sani Insan Muhamadi (Jurusan Pendidikan Guru Madrasah Ibtidaiyah, 2018)
This study aims to determine the learning activities of students before and after using the lecture method plus discussion and assignment. The method used is Classroom Action Research (CAR) through II cycles and each cycle consist of planning, implementation, observation, and reflection, with the number of student 40 people in class IV MI Nurul Huda Sukasari Bandung Regency. Student learning activities before using the lecture method plus discussion and assignment obtained 45,06% (not god), after using the lecture method plus discussion and assignment to get and increase in each cycle, in the first cycle it reached 61,40% (good enough) then the student learning activities increased in the cycle II became 92,21% (very good). Thrus there is a significant increase after using the lecture method plus discussion and assignmenton the moral principles of the noble subject.